2017
DOI: 10.12693/aphyspola.132.1466
|View full text |Cite
|
Sign up to set email alerts
|

Positronium Formation in Organic Liquids

Abstract: This paper reports on the results of positron annihilation lifetime measurements of three organic liquids: benzene (C6H6), cyclohexane (C6H12), and methanol (CH3OH). The lifetime spectra are acquired at different temperatures for non-degassed, degassed, and oxygen-saturated samples, at temperatures between 5 • C and 25 • C. The spectra are analyzed using a standard three-exponential model. The influence of oxygen on each lifetime and intensity component is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
2
1
0
Order By: Relevance
“…(6), also showed that the relative intensity I 3 decreases very fast from 10.13±0.9 % at annealing temperature 100°C to 1.4±0.02 % at annealing temperature 400°C. A similar behavior was also shown in the data reported by Karbowski et al [27], and is to be attributed to the sintering process. The relative intensity I 3 does not change noticeably and nearly constant at temperature above 400°C.…”
Section: Resultssupporting
confidence: 90%
“…(6), also showed that the relative intensity I 3 decreases very fast from 10.13±0.9 % at annealing temperature 100°C to 1.4±0.02 % at annealing temperature 400°C. A similar behavior was also shown in the data reported by Karbowski et al [27], and is to be attributed to the sintering process. The relative intensity I 3 does not change noticeably and nearly constant at temperature above 400°C.…”
Section: Resultssupporting
confidence: 90%
“…However, it should be noted that some of the detected Zn monovacancies could correspond to similarly sized open space at the grain boundaries, since the formation energy of Zn vacancies at grain boundaries is also relatively low compared to the case of pure ZnO [53]. The second lifetime component points to the presence of larger vacancy clusters which most likely are located at the grain boundaries, as was also proposed in some previous studies [50,54] and is inferred from the diffusion model analysis presented above in Sec. III C. The picture thus emerges that the as-deposited ZnO:Al layers contain Zn monovacancies inside the grains and larger vacancy clusters at their grain boundaries.…”
Section: E Evolution Of the Size Of Vacancies And Vacancy Clusters Asupporting
confidence: 65%
“…The third and fourth positron lifetimes are in the range of 1 to 5 ns, but show very low intensities between 0.2% and 3%, demonstrating that large voids and the corresponding formation of orthopositronium are nearly absent. For the top layer, a short lifetime τ 1 for the as-deposited sample of 224 ± 5 ps is obtained from the LT analysis, which is in the range of 220-240 ps reported for the Zn monovacancy [45,50]. The second lifetime τ 2 of 369 ± 9 ps is due to larger vacancy clusters [ Fig.…”
Section: E Evolution Of the Size Of Vacancies And Vacancy Clusters Amentioning
confidence: 94%